Emergency Department Utilization Among People Living With HIV on Chronic Opioid Therapy. (21st April 2021) - Thakarar, Kinna; Kulkarni, Amoli; Lodi, Sara; Walley, Alexander Y.; Lira, Marlene C.; Forman, Leah S.; Colasanti, Jonathan A.; del Rio, Carlos; Samet, Jeffrey H.
Chronic pain among people with HIV (PWH) is a driving factor of emergency department (ED) utilization, and it is often treated with chronic opioid therapy (COT). We conducted a cross-sectional analysis of a prospective observational cohort of PWH on COT at 2 hospital-based clinics to determine whether COT-specific factors are associated with ED utilization among PWH. The primary outcome was an ED visit within 12 months after study enrollment. We used stepwise logistic regression including age, gender, opioid duration, hepatitis C, depression, prior ED visits, and Charlson comorbidity index. Of 153 study participants, n = 69 (45%) had an ED visit; 25% of ED visits were pain-related. High dose opioids, benzodiazepine co-prescribing, and lack of opioid treatment agreements were not associated with ED utilization, but prior ED visits (p = 0.002), depression (p = 0.001) and higher Charlson comorbidity score (p = 0.003) were associated with ED utilization. COT-specific factors were not associated with increased ED utilization among PWH.